Model Intervensi Sosial Untuk Memperkuat Ketahanan Keluarga di Kelurahan Serang Kota Serang Provinsi Banten - Riny Handayani (WINDRADI: Jurnal Pengabdian Masyarakat, 2025)
Family resilience is a strategic issue in urban settings, particularly among families experiencing socioeconomic vulnerability. This community service program aims to develop a social intervention model to strengthen family resilience in Serang Subdistrict, Serang City. The implementation consisted of several stages, including an initial needs assessment, family education sessions, economic skills training, intensive family mentoring, and the establishment of a family support network to reinforce community-based social ties. The program outcomes indicate significant improvements in various aspects of family capacity: family knowledge increased by 60 percent, communication skills improved by 45 percent, and 70 percent of participants began applying better household financial management practices. Additionally, a family support group was formed, functioning as a social network where residents can share experiences, exchange information, and develop strategies for resilience building. These findings demonstrate that education-based and community empowerment interventions are effective in enhancing families’ abilities to manage social and economic pressures. The program also shows strong potential for replication in other subdistricts, provided that local contexts and community needs are appropriately considered.